Генератор для физического моделирования импульсных электромагнитных полей - Борцов, Александр Васильевич (НТУ "ХПИ", 2008)
Разработан и изготовлен генератор импульсных токов для физического моделирования импульсных электромагнитных полей. При разработке генератора использованы новейшие достижения в области полупроводниковой техники и компьютерное моделирование электромагнитных процессов в силовом контуре генератора. Получены новые формы импульсов разрядного тока – апериодический импульс, одна полуволна гармонического импульса, срезанная полуволна гармонического импульса.

A pulse current generator for physical simulation of pulsed electromagnetic fields has been developed and manufactured. The latest achievements in the field of semiconductor engineering are used in designing the generator, computer simulation of electromagnetic processes in the generator power circuit applied. New pulse forms are obtained, namely, aperiodic pulse, a half-wave of harmonic oscillation, a sheared half-wave of harmonic oscillation. New pulse forms are of great interest in simulation of electromagnetic processes in the plants for magnetic pulse treatment of metals.
A generator for physical simulation of pulsed electromagnetic fields
Keywords: магнитное поле; импульсные генераторы; полупроводниковая техника; электромагнитные процессы; магнитно-импульсные установки; источники энергии; pulse current generator; new pulse forms of discharge current